The intergenerational effects of parental incarceration - Will Dobbie; Hans Grönqvist; Susan Niknami; Mårten Palme; Mikael Priks (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
We estimate the causal effects of parental incarceration on children's short- and long-run out-comes using administrative data from Sweden. Our empirical strategy exploits exogenous varia-tion in parental incarceration from the random assignment of criminal defendants to judges with different incarceration tendencies. We find that the incarceration of a parent in childhood leads to a significant increase in teen crime and significant decreases in educational attainment and adult employment. The effects are concentrated among children from the most disadvantaged families, where criminal convictions increase by 10 percentage points, high school graduation decreases by 25 percentage points, and employment at age 25 decreases by 29 percentage points. In contrast, there are no detectable effects among children from more advantaged families. These results suggest that the incarceration of parents with young children may significantly increase the intergenerational persistence of poverty and criminal behavior, even in affluent countries with extensive social safety nets.
Keywords: 330; Strafvollzug; Familie; Jugendliche; Kriminalität; Armut; Schwangerschaft; Jugendarbeitslosigkeit; Schätzung; Schweden